The Problem of Ideology in Biblical Studies - Reed, Randall (Bulletin for the study of religion, 2011)
The issue of ideology is one which is still in need of discussion in biblical studies. In this article I will map the way that the various strains of social approaches to New Testament have started to address this issue, though often indirectly. I will then move to an explicit discussion of the issue making reference to the Marxist tradition focusing on Marx, Althusser and Žižek. I will argue that rather than the more traditional view which focuses on a non-ideological space like science, a better approach is one championed by Žižek which looks for gaps and cracks in the social world which then lend themselves to ideological criticism.